Tanzania : Can Conditional Cash Transfers Encourage Safer Sexual Behavior? - World Bank (Washington, DC, 2015)
Conditional cash transfer programs are often used to encourage poor families to take young children for regular health check-ups and enroll them in school decision making. Can cash transfers successfully cut transmission of human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) by reducing risky sexual behaviors? How can these programs be structured for maximum impact to help countries meet the challenges of reducing HIV and AIDS and other sexually transmitted diseases? The World Bank is working with the international community and governments to stop the spread of HIV and AIDS. The extraordinarily high social and economic cost of the HIV and AIDS crisis requires that governments and development experts continue the search for innovative and effective prevention approaches, including financial incentives. The results of the evaluation indicate the potential of financial incentives for reducing the spread of sexually transmitted infections and possibly as a route for HIV prevention.